Utilization of Android Technology for E-Menu at Cafe Cindy - Saro, David (Engineering and Technology International Journal, 2024)
In the digital era, technological advancements have significantly transformed the culinary industry, particularly through the implementation of Android-based e-menu applications. This study aims to develop and implement an e-menu application at Cafe CINDY to enhance operational efficiency and customer satisfaction. The research employs a mixed-methods approach, combining qualitative and quantitative methods, including interviews, surveys, and system analytics.The findings indicate that the e-menu application streamlines the ordering process, reduces errors, minimizes reprinting costs, and provides customers with a more interactive and informative experience. Additionally, the system aids in inventory management and customer preference analysis, allowing for more strategic marketing decisions. Overall, the implementation of the Android-based e-menu application at Cafe CINDY offers significant operational improvements and a competitive edge in the culinary industry.